ORIGIN AND IDENTITY: REREADING EXODUS AS A POLEMICAL NARRATIVE THEN (PALESTINE) AND NOW (AFRICA) - Bosman, Hendrik Ludolph (Scriptura, 2005)
For several decades the book of Exodus was the locus classicus for the struggle against colonialism and racial discrimination across Africa. This paper engages with the problem: How do we appropriate the book of Exodus theologically in a post-colonial Africa? The validity of the following hypothesis will be investigated: The book of Exodus can be interpreted as a polemical narrative concerned with origin of Israel as a nation, born within the crucible of slavery and forged by the guiding divine presence during the sojourn in the desert and at Mount Sinai. It is argued that there are similarities between elements of the Exodus narrative and certain texts in the Ancient Near East - specific attention will be given to the three major themes of the Baal epic: The crossing of the Re(e)d Sea (Ex 14-15) and Baal’s victory over Yam (sea); the instructions concerning the tabernacle and the eventual building of the tabernacle (Ex 25-31, 35-40) and the arguments for building a temple or palace for Baal; as well as the destruction of the golden calf (Ex 32-34) and the annihilation of Mot (death) by Anat. Brief mention is also be made of correspondences between the narratives in Exodus and certain Assyrian and Neo-Babylonian texts. In all these contexts it is suggested that Yahweh is portrayed as the deity that played a crucial role in the origin of Israel as a nation and that this was constitutive for emerging monotheism as the religious identity of Israel as a nation. In closing it will be reflected on how African narratives concerning origin and identity can engage in an intertextual dialogue with the Exodus narrative.